Bhabani Bhattacharya as a Novelist: A New Approach - Priydarshi, Ashok Kumar (Journal of Advanced Research in English & Education; Vol 5 No 3 (2020): Journal of Advanced Research in English & Education, 2021)
Bhabani Bhattacharya, the Sahitya Academy Award winner is among the major Indian novelists writing in English. His literary fame is not confined to India alone. His books have been translated into 26 languages, including 16 European languages. Being a humanist, he is greatly moved by the poverty, hunger and sufferings of the people. In his novels, he has exposed the various social evils of modern men hunger for food and freedom, prostitution, exploitation, superstition, hoarding of foodgrains etc. How to cite this article:  Priydarshi AK. Bhabani Bhattacharya as a Novelist: A New Approach. J Adv Res Eng & Edu 2020; 5(3): 6-8. DOI: https://doi.org/10.24321/2456.4370.202010